Long non-coding RNA mediated drug resistance in breast cancer. (July 2022) - Singh, Deepshikha; Assaraf, Yehuda G.; Gacche, Rajesh N.
Abstract: Breast cancer is one of the most prevalent cancers in women and a leading cause of mortality. As per the GLOBCAN report of 2021, breast cancer has surpassed lung cancer which until recently was the most commonly diagnosed cancer. Despite significant efforts to improve early detection and therapeutic efficacy of breast cancer, the frequent emergence of drug resistance remains the predominant basis for the poor prognosis of cancer patients harboring various malignancies. Long non-coding RNA (lncRNAs) are known to affect a variety of components of genome function, including epigenetics, gene transcription, splicing, translation, as well as many central biological processes like cell cycle progression, cell differentiation, development, and pluripotency. LncRNAs are dysregulated in various malignancies and interact with a multitude of RNAs and proteins to impact drug resistance. LncRNAs regulate chemoresistance in cancer by employing an assortment of molecular mechanisms including multidrug efflux, suppression of apoptosis, DNA damage response, epigenetic alterations, as well as functioning as competitive endogenous RNA. When combined with other regulatory mechanisms, these pathways form a complex orchestration of signaling that ultimately lead to chemoresistance. The current review delves into the role of lncRNAs in inducing drug resistance to conventional therapeutic anti-cancer drugs used for the treatment of breast cancer. We propose that lncRNAs that provoke drug resistance could be used to develop new targeted and tailored therapeutics providing a novel approach to introduce promising personalized treatment modalities to overcome chemoresistance in breast cancer patients. Hence, lncRNAs that drive anticancer drug resistance can be potentially explored as biomarkers of disease prognosis and may provide unique opportunities to circumvent chemoresistance in breast cancer patients.